Rethinking Halal : Genealogy, Current Trends, and New Interpretations - Christians, Louis-Léon; Yakin, Ayang Utriza (Muslim Minorities, 2021)
"This book invites to rethink certain aspects of halal, and in particular the issue of the halal market and halal certification in Muslim-minority contexts. Rather than limiting itself to elucidating the doctrinal traditions relating to halal/haram, or on the contrary, focusing only on the external economic, financial, political or demographic factors that explain the changes taking place, Rethinking Halal shows the need to underline the points of balance between the aspects of religious doctrine on the one hand and the economic or political contextual aspects on the other hand. Through the study of various countries, Rethinking Halal demonstrates that Islam underwent a process of positivisation, that is, a kind of reframing of its rules and principles through the lens of a characteristically modern standardising, scientificising, and systematising mind. Contributors are Ayang Utriza Yakin, Louis-Léon Christians, Baudouin Dupret, Jajat Burhanudin, Syafiq Hasyim, Zaynab El Bernoussi, En-Chieh Chao, Rossella Bottoni, Lauren Crossland-Marr, Konrad Pędziwiatr, Matteo Benussi, Harun Sencal and Mehmet Asutay"--